Epidemiological profile and obstetric outcomes of patients with peripartum congestive heart failure in Taiwan: a retrospective nationwide study - Ying-Jen Chang; Chung-Han Ho; Jen-Yin Chen; Ming-Ping Wu; Chia-Hung Yu; Jhi-Joung Wang; Chia-Ming Chen; Chin-Chen Chu (BMC, 2017)
Abstract Background During pregnancy, the hyperdynamic physiology of circulation can exacerbate many cardiovascular disorders. Congestive heart failure (CHF) usually occurs during late pregnancy, which is significantly associated with a high level of maternal and neonatal morbidities and mortalities. The profile of women who develop peripartum CHF (PCHF) is unknown. We investigated the epidemiological profiles of PCHF. Methods In this retrospective cohort study, PCHF patients were identified using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes in Taiwan's National Health Insurance Research Database. Risk factors and obstetric outcomes were compared in women with and without PCHF. Results From 2,115,873 birth-mothers in Taiwan between 1997 and 2013, we identified 512 with PCHF (incidence: 24.20/105). More women with than without PCHF were older (≥ 35, 18.16% vs. 9.62%), and had more multifetal gestations (7.42% vs. 1.40%), gestational hypertension (HTN) (19.2% vs. 1.31%), and gestational diabetes mellitus (4.10% vs. 0.67%). After the analysis had been adjusted for confounders, the leading comorbidities associated with PCHF were structural heart diseases (adjusted odds ratio [aOR]: 67.21; 95% confidence interval [CI]: 54.29-83.22), pulmonary diseases (aOR: 13.12; 95% CI: 10.28-16.75), chronic HTN (aOR: 11.27; 95% CI: 6.94-18.28), thyroid disease (aOR: 9.53; 95% CI: 5.27-17.23), and gestational HTN (aOR: 5.16; 95% CI: 3.89-6.85). PCHF patients also had a higher rate of cesarean sections (66.41% vs. 34.46%; p < 0.0001). Conclusion Maternal structural heart diseases, pulmonary diseases, thyroid disorders, and preexisting or gestational HTN are associated with a higher risk of developing PCHF. Birth-mothers with PCHF also had a higher risk of caesarean section and adverse outcomes, including maternal death. Our findings should benefit healthcare providers, and government and health insurance policy makers.